PENERAPAN STRATEGI PEMBELAJARAN SCAFFOLDING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 1 PERHENTIAN RAJA - Astuti, Dewi Puji; Rasmiwetti, Rasmiwetti; Abdullah, Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The research using scaffolding learning strategies has been done onthe subject of colloids in class XI IPA SMAN 1 Perhentian Raja. This study aims toknowed improved student achievement on the subject of colloids with the application ofscaffolding learning strategies and student achievement improvement category. Thisresearch was a form of experimental research with the draft design randomized controlgroup pretest-posttest. The study population was all students of class XI IPA at SMAN 1Perhentian Raja. The samples were students of class XI IPA 2 as experimental class andclass XI IPA 1 as the control class. The experimental class was applied scaffoldinglearning strategies, while the control class using discussion method. Data wereanalyzed using t-test. Results from the study showed t count > t table (5,97 > 1,67),meaning that the application of scaffolding learning strategies can improve studentachievement on the subject of colloids in class XI IPA SMAN 1 Perhentian Raja. Theraising student achievement category in the experimental class including normalizedgain a high score of 0,76.Keywords : Scaffolding Learning Strategies, Student Achievement, Colloid